2019
DOI: 10.5713/ajas.18.0057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary cotton stalk on nitrogen and free gossypol metabolism in sheep

Abstract: With short-term CS administration, only a small amount of FG is retained in the body. In response to long-term or high-FS CS feeding, however, FG accumulates in, and damages, the liver and kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Some researchers have shown that long-term feeding of excessive amounts of nondetoxified cotton by-products (e.g., cotton leaves, cottonseed meal, and cotton stalks) to vertebrates can lead to the accumulation of free gossypol (FG) in the fed animals, causing poisoning and acute respiratory distress, anorexia, fatigue, and even death [86][87][88]. This has hindered the application of cotton stalks as fodder.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have shown that long-term feeding of excessive amounts of nondetoxified cotton by-products (e.g., cotton leaves, cottonseed meal, and cotton stalks) to vertebrates can lead to the accumulation of free gossypol (FG) in the fed animals, causing poisoning and acute respiratory distress, anorexia, fatigue, and even death [86][87][88]. This has hindered the application of cotton stalks as fodder.…”
Section: Discussionmentioning
confidence: 99%
“…Its toxic effects have been recorded in non-ruminants and ruminants (Gadelha et al, 2014). Ruminants have however the ability to detoxify the free gossypol concentration by binding it with ruminal microbial proteins (Rehemujiang et al, 2019). But this ability is reduced when gossypol intake exceeds rumen detoxification capacity (Morgan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when dairy cows were fed with a diet supplemented with 717 mg/kg and 951 mg/kg of free gossypol for 170 days, the pregnancy rate decreased and the incidence of abortion increased [11]. Dietary gossypol can significantly reduce body weight in sheep and cause liver cell swelling, nuclear lysis, and kidney cell necrosis [12]. Dietary gossypol also decreases blood glucose and insulin levels, increases insulin sensitivity, and improves lipid metabolism in rats with type 2 diabetes [13].…”
Section: Introductionmentioning
confidence: 99%